1970
DOI: 10.1677/joe.0.0460425
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of Progesterone to Affect Myometrial Activity in the Guinea-Pig

Abstract: SUMMARY A study was made of the effects of both systemic and intrauterine progesterone and medroxyprogesterone acetate (MPA) administration on the duration of pregnancy in the guinea-pig. In no case was pregnancy prolonged beyond normal term. When progesterone and MPA were administered to non-pregnant guinea-pigs (in doses up to 50 times that required to block myometrial activity in the rabbit) there was no effect on the amplitude and frequency of intrauterine pressure cycles recorded in vivo by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…However, the significant increase in the amplitude of the pressure cycles is contrary to the well-documented findings of a depressant effect of the corpus luteum on myometrial activity in the rabbit (Knaus, 1926;Allen & Corner, 1929;Schofield, 1957), human female (Knaus, 1934;Csapo & Pinto-Dantas, 1966;Coutinho, 1968) and cow (Evans & Miller, 1936;Porter, unpublished work) in vivo, and sow (Keye, 1923) and cow (Cupps & Asdell, 1944) in vitro. Although this apparent species difference cannot be explained as yet, it is consistent with earlier findings (Porter, 1969(Porter, , 1970 that exogenous progesterone had no inhibitory action upon myometrial activity in the non-pregnant guinea-pig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the significant increase in the amplitude of the pressure cycles is contrary to the well-documented findings of a depressant effect of the corpus luteum on myometrial activity in the rabbit (Knaus, 1926;Allen & Corner, 1929;Schofield, 1957), human female (Knaus, 1934;Csapo & Pinto-Dantas, 1966;Coutinho, 1968) and cow (Evans & Miller, 1936;Porter, unpublished work) in vivo, and sow (Keye, 1923) and cow (Cupps & Asdell, 1944) in vitro. Although this apparent species difference cannot be explained as yet, it is consistent with earlier findings (Porter, 1969(Porter, , 1970 that exogenous progesterone had no inhibitory action upon myometrial activity in the non-pregnant guinea-pig.…”
Section: Discussionsupporting
confidence: 91%
“…Zarrow, Anderson & Callantine (1963) and Schofield (1964) reported that parturition in the guinea-pig could not be delayed by the systemic administration of progesterone. Not only was this confirmed recently (Porter, 1969(Porter, , 1970, but it was also found that even the intrauterine administration of large doses of progesterone failed to prevent delivery occurring at the normal time. Furthermore, in the non-pregnant animal, neither systemic nor intrauterine progesterone treatment had an effect upon the mechanical activity of the uterus in vivo ; a finding in contrast to the well documented effects of progesterone on myometrial activity in the rabbit (Csapo & Takeda, 1965;Porter, 1968).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The idea of progesterone withdrawal as a prerequisite for parturition is, however, not valid in all species. In guinea pig (Porter 1970) and human pregnancy (Yannone et al 1968, Tulchinsky et al 1972) progesterone levels do not decline before the onset of labor and in human pregnancy (Lofgren & Backstrom 1997) high progesterone concentrations during parturition appeared to be related to effective labor. Interestingly, Vallet et al (1990) observed an increase in ewe uterine OTR following 12 days progesterone treatment and in accordance with the present results, Ruzycky & Crankshaw (1988) observed no inhibitory effect of progesterone on oxytocin induced uterine contractility in estrogen dominated rats.…”
Section: Discussionmentioning
confidence: 92%